Research on the Influence of Dust Suppressants on the Coupling Behavior of Dust–Mist Particles - Ming Li; Donald Lusambo; Usman Muhammad Tukur; Moses Masiye; Wending Li; Haochen Lian (Applied Sciences)
Spray dust removal is currently the primary method of dust control technology, while it exhibits low efficacy in dust removal capability. A Phase Doppler Particle Analyzer (PDPA) experimental system was constructed to study the influence of dust suppressants on the coupling behavior of dust–mist particles using comparative methods. According to the experimental results of the atomization effect of the spray, the Sauter Mean Diameter (D32) of the mist size of the dust suppressants showed an increasing trend compared to water. This trend became less obvious with an increase in spray pressure, and a reduction in the surface tension of the dust suppressants promoted an increase in the particle size distribution of water mist. According to the test results of the dust–mist coupling behavior experiment, compared with water, the coupling efficiency of Dodecyl Alcohol (DA), Alkylphenol Polyoxyethylene (OP-10), and Sodium Dodecyl Sulfate (SDS) increased by 27.0%, 20.3%, and 15.0%, respectively. This indicates a proportional relationship between the wetting performance of the dust suppressants and the dust–mist coupling rate and an inverse relationship between the surface tension of the dust suppressant solutions and the dust removal efficiency. The research findings hold major possibilities for enhancing the dust removal efficiency.